Mayer-Rokitansky syndrome: presentation of six cases and review of literature - Medina, Ruth (2015)
The digenesia Müller ducts or agenesis of the uterus and vagina, known as Mayer-Rokitansky-Kuster-Hauser syndrome is a disorder of the female reproductive characterized by primary amenorrhea and abnormalities associated with urogenital tract. We present six cases of patients with Mayer-Rokitansky syndrome, describe the clinical presentation, management, and we review the literature.